Anúncios de jornais de Mato Grosso dos séculos XIX e XX : características filológicas - Jesus, Ivanete Maria de (2016)
The current research has the purpose to analyze mato grosso’s newspaper advertisements from nineteenth and twentieth centuries, from 1848 to 1927, selected microfilmed testemonies from the Núcleo de Documentação e Informação Histórica Regional – NDIHR, from the Universidade Federal de Mato Grosso, that will be presented in the facsimile edition format, which impacts in a low level – near zero - on the original text edition, and from what there will be done the study of the orthographic occurences and of the aspects related to the transcendental function of the Philology, considering the Philology as its theoretical basis, as defined by Spina (1997, p. 77) and Melo (1981, p. 7), et al. This research aims to facilitate the approach to the corpus for researchers from connected knowledge areas and is attached to the research project “Para a História do Português Brasileiro – Mato Grosso – PHPB-MT”.